2022
DOI: 10.1002/adma.202108408
|View full text |Cite
|
Sign up to set email alerts
|

Miniaturized Multispectral Detector Derived from Gradient Response Units on Single MAPbX3 Microwire

Abstract: Miniaturized multispectral detectors are urgently desired given the unprecedented prosperity of smart optoelectronic chips for integrated functions including communication, imaging, scientific analysis, etc. However, multispectral detectors require complicated prism optics or interference/interferometric filters for spectral recognition, which hampers the miniaturization and their subsequent integration in photonic integrated circuits. In this work, inspired by the advance of computational imaging, optical‐com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
31
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 55 publications
0
31
0
Order By: Relevance
“…12−18 Xu et al demonstrated a miniaturized multispectral detector based on a composition-gradient perovskite microwire detector array, offering a response edge ranging from 450 to 790 nm. 19 However, such technologies require customized epitaxial growth for the composition-gradient micro/nanowire semiconductors followed by transfer of a single nanowire on the device substrate, which inevitably results in large-scale fabrication, which remains challenging. The shape, length, and composition gradient of each nanowire could not be the same, leading to limited performance repeatability.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…12−18 Xu et al demonstrated a miniaturized multispectral detector based on a composition-gradient perovskite microwire detector array, offering a response edge ranging from 450 to 790 nm. 19 However, such technologies require customized epitaxial growth for the composition-gradient micro/nanowire semiconductors followed by transfer of a single nanowire on the device substrate, which inevitably results in large-scale fabrication, which remains challenging. The shape, length, and composition gradient of each nanowire could not be the same, leading to limited performance repeatability.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Miniaturized spectrometers with advantages of portability and low cost and power consumption have attracted much attention due to their potential in advanced application scenarios, including wearable devices, hyperspectral imaging, and internet of things. Computational spectrum reconstruction based on a series of response-modulated photodetectors with a gradient bandgap is one of the most promising methods for achieving such miniaturized spectroscopy systems. For instance, Yang et al successfully demonstrate a miniaturized spectrometer at the scale of tens of micrometers using a single compositionally graded CdS x Se 1– x nanowire . Recently, halide perovskites have also been used in photodetectors for human visual-like spectrum projection, full-color detection, and multispectral recognition owing to their outstanding properties such as facile solution-process fabrication, excellent light harvesting coefficients, and tunable bandgaps. Xu et al demonstrated a miniaturized multispectral detector based on a composition-gradient perovskite microwire detector array, offering a response edge ranging from 450 to 790 nm . However, such technologies require customized epitaxial growth for the composition-gradient micro/nanowire semiconductors followed by transfer of a single nanowire on the device substrate, which inevitably results in large-scale fabrication, which remains challenging.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6][7] Compared to the conventional charge-coupled device (CCD) equipped with perovskite microwires, and perovskite QD films have been realized by the spectral reconfiguration algorithm, which can accurately identify the spectrum over a wide range of wavelengths with high resolution. [34][35][36][37][38][39] Besides accurate identification of the spectrum information, the integrated flexible color-cognitive devices are also important due to their ability to meet the miniaturization and integration of wearable devices, but the device integration with the smaller footprint remains challenging.…”
Section: Introductionmentioning
confidence: 99%
“…Benefiting from the prosperity of micro- and nanofabricating processes in past decades, the miniaturization of optics with the incorporation of compatible micro-electromechanical systems (MEMS) facilitates the evolution of size in multispectral photodetectors, whereas the miniaturizing of optics and its complicated splitting light path design significantly increase the complexity of device architecture and make multispectral sensing devices stringent and costly for large-scale manufacture. Alternatively, a response-modulated photodetector array with the assistance of a computational recursive algorithm provides a possibility for spectral discrimination without additional optical components. Recently, successful spectral discrimination in the visible range has been demonstrated in a compositionally engineered CdS x Se 1– x nanowire, an MAPbX 3 microwire, and MAPbX 3 films with a gradient bandgap, and in the infrared range, it has also been realized by black phosphorus and two-dimensional heterojunctions through electrical tuning, making them promising candidates for miniaturized multispectral photodetectors. These devices indeed exhibit a real-time spectral discrimination with an accuracy of about nanometers .…”
mentioning
confidence: 99%
“…Alternatively, a response-modulated photodetector array with the assistance of a computational recursive algorithm provides a possibility for spectral discrimination without additional optical components. 12−14 Recently, successful spectral discrimination in the visible range has been demonstrated in a compositionally engineered CdS x Se 1−x nanowire, 15 an MAPbX 3 microwire, 16 and MAPbX 3 films with a gradient bandgap, 17 and in the infrared range, it has also been realized by black phosphorus 18 and twodimensional heterojunctions through electrical tuning, 19 making them promising candidates for miniaturized multispectral photodetectors. These devices indeed exhibit a realtime spectral discrimination with an accuracy of about nanometers.…”
mentioning
confidence: 99%